Synthesis and characterization of mixed-ligand silver(I) saccharinate complex containing (2-(2-pyridyl)benzimidazole - Mario Ceroni Galloso; Jorge Reynaldo Angulo-Cornejo; Maria Nieves Lino-Pacaheco; Claudia Cecilia Villanueva Huerta; Enzo Martín Casimiro Soriano (Revista Colombiana de Química, 2018)
A new silver coordination compound [Ag(sac)(pbi)] was synthesized by reaction of silver(I) saccharinate with 2-(2-pyridyl)benzimidazole (pbi) in 64% yield. The characterization was performed by elemental analysis, IR, UV-Visible, XPS, 1H-NMR, and 13C-NMR spectroscopy. According to the results, silver is coordinating through three nitrogen atoms: one from saccharinate and the others from 2-(2-pyridyl)benzimidazole forming with this ligand a five-membered chelate ring.